Pseudoinfectious mononucleosis: a presentation ofBartonella henselae infection. Issue 5 (1st November 2000) - Massei, F; Messina, F; Massimetti, M; Macchia, P; Maggiore, G
Abstract : Six children presented during one year with clinical features of infectious mononucleosis, but with laboratory findings of leucocytosis with neutrophilia, increased erythrocyte sedimentation rate, and hypergammaglobulinaemia. Serology for Epstein–Barr virus, cytomegalovirus, adenovirus, and Toxoplasma gondii was negative, while anti- Bartonella henselae IgM with high IgG titre (⩾1/1024) was present in all. All children had contact with kittens. No specific treatment was administered and all recovered.